Assessment of morpho-physiochemical and cooking traits of extant varieties of rice (Oryza sativa) of India - MONIKA A JOSHI; S. K. CHAKRABARTY; YOGENDRA SINGH; MALAVIKA DADLANI (Seed Research, 2026)
Fifty eight prominent extant rice varieties of Indian origin that are in active seed production chain were screened for their grain, morphological, physiochemical and cooking properties, to establish relationship between them so as to predictthe cooking quality of a variety on the basis of phenotypic characteristics. The length and breadth of milled raw rice varied from 6.1 mm (Jaishree) to 10.7 mm (Pusa Basmati 1) and 1.97 mm (PKV-HMT) to 3.28 mm (Kranthi), respectively. Majority of the varieties were long bold (18) and short bold (11) in shape; with only nine of the extant varieties categorized as basmati type and only five as extra long slender. Considerable range was recorded for grain colour (white to greyish orange); with majority of them being greyish white in colour. The amylose content (AC) was intermediate to high in most of the varieties and ranged from 6.28% (Govind) to 29.7% (Ambey Mohar). The gelatinization temperature (GT), as indexed by the alkali disintegration pattern, revealed that most of the varieties had low alkali values. High heritability coupled with moderate to high genetic advance and genetic co-efficient of variation (GCV) indicate the predominance of additive gene action for these two traits viz. AC and GT, thereby, emphasizing that selection based methods would be rewarding. No variety with low amylose and high alkali value was observed, suggesting that the varieties in the seed chain are selected for their good cooking quality. Further, some varieties that were superior with high amylose and GT could be utilized in breeding programmes for improving the cooking quality.